Vacuum ultraviolet photoionization and dissociative photoionization of toluene: Experimental and theoretical insights. Issue 5 (October 2021) - Zhao, Yujie; Huang, Pei; Li, Li; Zhan, Yousheng; Wang, Ke; Yang, Haohang; Jin, Jianhui; Chen, Yuqian; Liu, Yibao; Sheng, Liusi; Chen, Jun; Cao, Maoqi
The photoionization and dissociative photoionization of toluene have been studied using synchrotron radiation vacuum ultraviolet light with photon energy in the range of 8.50–25.50 eV. The ionization energies (8.82 eV) and double ionization energies (23.80 eV) of toluene as well as the appearance energies for its major fragments C7 H7 + (11.17/10.71 eV), C6 H5 + (13.73 eV), C5 H6 + (13.58/12.50 eV), C5 H5 + (16.23 eV), C4 H5 + (15.64 eV), C4 H4 + (16.10 eV) and C4 H3 + (17.11 eV) are determined, respectively by using photoionization efficiency spectrometry. With the help of experimental and theoretical results, seven dissociative photoionization channels have been proposed: C7 H7 + + H, C6 H5 + + CH3, C5 H6 + + C2 H2, C5 H5 + + C2 H2 + H, C4 H5 + + C3 H3, C4 H4 + + C3 H4 and C4 H3 + + C3 H4 + H. In addition, the geometries of the intermediates, transition states and products involved in these photoionization and dissociative photoionization processes have been performed at the B3LYP/6-311++G(d, p) level. The mechanisms of dissociative photoionization of toluene and the intermediates and transition states involved are discussed in detail. Generally speaking, the experimental results are in agreement with theoretical calculations in this work and published literature results. Especially the mechanisms of dissociative photoionization to C4 H5 +, C4 H4 + and C4 H3 + were discussed for the first time in this work. This investigation may provide useful information on understanding the photoionization and dissociative photoionization of toluene.